2004
DOI: 10.1021/la0492153
|View full text |Cite
|
Sign up to set email alerts
|

Micellization of Non-Surface-Active Diblock Copolymers in Water. Special Characteristics of Poly(styrene)-block-Poly(styrenesulfonate)

Abstract: Strongly ionized amphiphilic diblock copolymers of poly(styrene)-b-poly(styrenesulfonate) with various hydrophilic and hydrophobic chain lengths were synthesized by living radical polymerization, and their properties and self-assembling behavior were systematically investigated by surface tension measurement, foam formation, hydrophobic dye solubilization, X-ray reflectivity, dynamic light scattering, small-angle neutron scattering, small-angle X-ray scattering, and atomic force microscope techniques. These co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
106
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(118 citation statements)
references
References 39 publications
11
106
1
Order By: Relevance
“…However, highly cationic polymers (specifically LC10-h and HC10-h) had surface tensions similar to that of pure water at 72 mN m À1 (Table 1) despite the hydrophobic functionality. Similarly, in an investigation of polymers with low polydispersity at an airewater interface, Matsuoka et al (2004) also found that charged polymers exhibited 'non-surface activity' despite the presence of hydrophobic groups. Polymer accumulation at the air-liquid interface is theorised to occur as hydrogen bonding with OH À or H þ groups (Yang et al 2001), which translates to air-liquid surface adsorption without surface penetration.…”
Section: Bubble Coating With Hydrophobically Functionalised Polymersmentioning
confidence: 91%
“…However, highly cationic polymers (specifically LC10-h and HC10-h) had surface tensions similar to that of pure water at 72 mN m À1 (Table 1) despite the hydrophobic functionality. Similarly, in an investigation of polymers with low polydispersity at an airewater interface, Matsuoka et al (2004) also found that charged polymers exhibited 'non-surface activity' despite the presence of hydrophobic groups. Polymer accumulation at the air-liquid interface is theorised to occur as hydrogen bonding with OH À or H þ groups (Yang et al 2001), which translates to air-liquid surface adsorption without surface penetration.…”
Section: Bubble Coating With Hydrophobically Functionalised Polymersmentioning
confidence: 91%
“…To conclude this CMC discussion, one should note that the presence of free unimers in solution of amphiphilic diblocks with low CMC is not specific to radical polymerization samples. Free unimers have also been observed in solution of Poly(tertbutyl Styrene)-Poly(Styrene Sulfonate) [6] and Poly(Styrene)-Poly(Acrylic Acid) [34] diblocks in water, although these systems had been synthesized by anionic polymerization and form frozen core objects.…”
Section: A Double Population Of Diblocks In Solutionmentioning
confidence: 99%
“…Previously, 2 we studied the non-surface active nature of PS-b-PSS; the surface tension of the solution did not decrease and no foam was observed under a no salt condition, while it changed into surface active by salt additon. In this study, to make the origin of the non-surface activity clearer, we examined the nature of random copolymer of styrene and styrenesulfonate in additon to that of the PSS homopolymer.…”
mentioning
confidence: 96%
“…2 The degree of polymerization was m:n = 57:59. Surface tension of the solutions of random, homo, and block copolymers, measured with FACE CBVP-Z Surface Tensiometer (Kyowa Interface Science, Tokyo) is shown in Figure 1 together with the observation of foam formation.…”
mentioning
confidence: 99%
See 1 more Smart Citation